2018
DOI: 10.1038/s41467-018-06709-w
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional molecular modulators for perovskite solar cells with over 20% efficiency and high operational stability

Abstract: Perovskite solar cells present one of the most prominent photovoltaic technologies, yet their stability, scalability, and engineering at the molecular level remain challenging. We demonstrate a concept of multifunctional molecular modulation of scalable and operationally stable perovskite solar cells that exhibit exceptional solar-to-electric power conversion efficiencies. The judiciously designed bifunctional molecular modulator SN links the mercapto-tetrazolium (S) and phenylammonium (N) moieties, which pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
263
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(270 citation statements)
references
References 37 publications
3
263
1
3
Order By: Relevance
“…The peaks at 1580 and 1307.5 cm −1 are respectively corresponding to the carboxylate and pyridine of PbPyA 2 , which reveals existence of PbPyA 2 in the perovskite film after annealing. [40] In Figure 1e, the control film shows peaks of metallic Pb located at 141.9 and 136.4 eV while suppressed in the doped film. Meanwhile, X-ray photoelectron spectroscopy (XPS) is conducted to further verify the change of chemical bonding states of Pb and I after incorporating with PbPyA 2 .…”
Section: Resultsmentioning
confidence: 95%
“…The peaks at 1580 and 1307.5 cm −1 are respectively corresponding to the carboxylate and pyridine of PbPyA 2 , which reveals existence of PbPyA 2 in the perovskite film after annealing. [40] In Figure 1e, the control film shows peaks of metallic Pb located at 141.9 and 136.4 eV while suppressed in the doped film. Meanwhile, X-ray photoelectron spectroscopy (XPS) is conducted to further verify the change of chemical bonding states of Pb and I after incorporating with PbPyA 2 .…”
Section: Resultsmentioning
confidence: 95%
“…The combination of these two passivating molecules shows the synergistic effect of passivating both the positively charged under‐coordinated Pb 2+ and negatively charged PbX 3 − anti‐sites defects. Bi et al . described on the multifunctional molecular modulator of 3‐(5‐mercapto‐1 H ‐tetrazol‐1‐yl)benzenaminium iodide, composed of hydrophobic heteroaromatic cores functionalized by ammonium (‐NH 3 + ) and thiol groups (‐SH).…”
Section: Defect Passivation In Metal Halide Perovskitesmentioning
confidence: 99%
“…4) The fourth functionality is associated with the enlargement in grain size induced by the thiol groups. The growth of monolithic‐type and/or large perovskite grains in polycrystalline films is a widely employed strategy to reduce detrimental defects . Although several groups have reported that amino‐functionalized groups are efficient for passivating under‐coordinated PbI 6 octahedra (Table S2), Xu et al .…”
Section: Defect Passivation In Metal Halide Perovskitesmentioning
confidence: 99%
“…[36][37][38][39][40] We therefore probed the long-term performance of 2D perovskite solar cells (Figure 8) by measuring the stability under inert and humid ambient air conditions ( Figure 8a and Figure S14, Supporting Information, respectively). [36][37][38][39][40] We therefore probed the long-term performance of 2D perovskite solar cells (Figure 8) by measuring the stability under inert and humid ambient air conditions ( Figure 8a and Figure S14, Supporting Information, respectively).…”
Section: Long-term Stabilitymentioning
confidence: 99%